2019
DOI: 10.1038/s41388-019-0906-3
|View full text |Cite
|
Sign up to set email alerts
|

REX1 promotes EMT-induced cell metastasis by activating the JAK2/STAT3-signaling pathway by targeting SOCS1 in cervical cancer

Abstract: ZFP42 zinc finger protein (REX1), a pluripotency marker in mouse pluripotent stem cells, has been identified as a tumor suppressor in several human cancers. However, the function of REX1 in cervical cancer remains unknown. Both IHC and western blot assays demonstrated that the expression of REX1 protein in cervical cancer tissue was much higher than that in normal cervical tissue. A xenograft assay showed that REX1 overexpression in SiHa and HeLa cells facilitated distant metastasis but did not significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…In the current study, our data showed that treatment with resveratrol, S3I201, or AG490 resulted in (58)(59)(60). We showed that resveratrol and S3I201 or AG490 consistently decreases phosphorylation of STAT3 Tyr705 in Hela cells and SiHa cells.…”
Section: Discussion the Cervical Cancer Cell Line Hela And Siha Cellsmentioning
confidence: 58%
“…In the current study, our data showed that treatment with resveratrol, S3I201, or AG490 resulted in (58)(59)(60). We showed that resveratrol and S3I201 or AG490 consistently decreases phosphorylation of STAT3 Tyr705 in Hela cells and SiHa cells.…”
Section: Discussion the Cervical Cancer Cell Line Hela And Siha Cellsmentioning
confidence: 58%
“…Studies have demonstrated that the activation of STAT3 signaling promotes metastasis of cervical cancer cells. [60][61][62] S3I201 inhibits STAT3, while AG490 is an inhibitor of the JAK upstream of STAT3. Our study indicated that RES had similar effects to S3I201 and AG490, resveratrol combined with S3I201 or AG490, and consistently decreased phosphorylation levels of STAT3 Tyr705 in HeLa and SiHa cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-19 has also been found to promote the progression of osteosarcoma by targeting and downregulating SOCS-6 in association with JAK2/STAT3 signaling [36]. The JAK2/STAT3 signaling pathway is involved in the progression of several cancers and is associated with other SOCS proteins through feedback regulation in various cell processes [37][38][39][40]. Although the research on JAK2/STAT3 signaling and mitochondrial fragmentation is limited, one study has proposed that JAK2/STAT3 signaling can prevent myocardial IR injury by reducing IR-induced mitochondrial oxidative damage [41].…”
Section: Discussionmentioning
confidence: 99%